O espaço das sequências mid somáveis e operadores mid somantes - Dias, Ricardo Ferreira (2017)
The main goal of this work is to study a new sequence space introduced in 2014 by Karn and Sinha, namely the space of mid p-summable sequences. More speci cally, we will study a recent work by G. Botelho and J.R. Campos, which deepens the seminal study of this space and presents new classes of operators involving the new space and the classical sequence spaces of absolutely and weakly p-summable sequences, called absolutely mid p-summing and weakly mid p-summing operators. From this, we study a new factorization theorem, involving these new classes of operators, for the absolutely p-summing operators.